Simulated car driving and its association with cognitive abilities in patients with schizophrenia - Fuermaier, Anselm B. M.; Weisbrod, Matthias (Schizophrenia research, 2019)
Objectives - Patients with schizophrenia commonly suffer from impairments in various aspects of cognition. These deficits were shown to have detrimental effects on daily life functioning and might also impair car driving. This study is the first to examine driving behaviour of patients with schizophrenia using an advanced driving simulator, and to explore the role of cognitive abilities of people with schizophrenia for driving. - Methods - Non-acute patients with schizophrenia (n=31) and healthy comparison participants (n=31) performed a comprehensive neuropsychological assessment and driving simulator rides. Neuropsychological and driving performances were compared between groups. Moreover, associations were explored between cognitive functions and driving behaviour in the entire group. - Results - Patients with schizophrenia revealed impairments in multiple aspects of cognition. In the driving simulator, patients with schizophrenia showed no indication of deviant driving in terms of number of collisions or reacting to critical situations, and even showed better lane control compared to healthy individuals. However, patients with schizophrenia drove significantly slower than healthy individuals, and caused more hindrance to the car behind while merging on the motorway. Slower driving was associated with lower test scores on attention and processing speed. Hindering the car behind was associated with test performance on planning and inhibition. - Conclusions - It is concluded that driving of patients with schizophrenia is characterized by a relatively slow speed, and can also be impaired in certain aspects, i.e. hindering a car behind while merging. Cognitive functions are crucial for driving, and should be target of treatment.
Available online 13 September 2018
Gesehen am 11.07.2019